Impact of the primary contact physiotherapy practitioner role on emergency department care for patients with musculoskeletal injuries in New South Wales. (30th September 2019) - Alkhouri, Hatem; Maka, Katherine; Wong, Lilian; McCarthy, Sally
Abstract: Objectives: To determine the impact of the emergency physiotherapy service provided through different models of care on service quality indicators, patient flow, staff and patient satisfaction. Method: A mixed method prospective observation study was conducted between September 2014 and April 2015 in 19 EDs where a physiotherapy service is provided. Results: Patients seen by the primary contact physiotherapist (PCP) were associated with a significant reduction in ED length of stay by 108 min, wait time to treatment by 10 min ( n = 4 EDs) and time‐to‐first analgesia by 18 min ( n = 19 EDs) compared to those seen through usual care processes. Patients who received care by a doctor first and then physiotherapist (secondary contact model) had a prolonged length of stay compared to other care pathways. High levels of satisfaction with the PCP role were expressed by ED staff ( n = 17 EDs) and patients ( n = 19 EDs). More than 95% of patients who received care by PCP were satisfied with the management of their condition, understood the advice and discharge information provided and had enough time to ask questions. Conclusion: ED implementation of the PCP model may improve patient flow and efficiency of clinical skill utilisation in a complex, high demand workplace.